Propuesta de organización de eventos en la plaza rodolfo baquerizo moreno para integrar los juegos tradicionales en la actividad turística de la ciudad de Guayaquil - Mendez M., Andrea (2009)
Nowadays, traditional games are not considered within our city´s touristic activity, because of that in this work, the important part is getting people to take conscience respect to the rescue of this kind of games, which in some countries of Europe and Latin America are the fundamental key of the touristic development. Through statistical results obtained in the feasibility study of this thesis, we noted the interest of the people consulted to participate and assist in the preservation of this intangible resource. That is why there is a proposal which will focus on three events, which will take place in the Plaza Rodolfo Baquerizo Moreno, which can be applied in order to disseminate the practice and knowledge of traditional games.